Implementation of the Qur'an Study Program in Improving Reading Ability and Memorize the Quran - Vina Syayidatul Fitriya; Pujiono Pujiono; Mustajab Mustajab (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
The ability to read and write the Qur'an is very important for students because it can understand and gain new knowledge derived from the Qur'an. Many students have not mastered how to read the Qur'an well and correctly. One factor is the family environment factor that lacks knowledge about reading the Qur'an. Therefore, it is necessary for every school to implement a Qur'an reading program so that students can learn to read the Qur'an well and correctly. This study aims to describe the Al-Qur'an deepening program for beginner, tahsin, pre-tahfidz and tahfidz classes in improving the ability to read and memorize the Qur'an at Darussyafa'ah Genteng Banyuwangi Middle School. The research approach used is a qualitative approach with a case study research type. The results of the study show that the implementation of learning in beginner, tahsin, pre-tahfidz, and tahfidz classes has a uniform sequence of activities, which begins with greetings, muhadarah, reading Al-Fatihah, and opening prayers, then continued with classical sessions and deposits, and closed with prayers and greetings. In terms of methodology, the beginner, tahsin, and pre-tahfidz classes use the Yanbua method, while the tahfidz class uses the setor method. The evaluation system at all levels includes mid-semester, end-of-semester, and class promotion exams, with additional quality improvement evaluations specifically for the tahsin class.